MANAGEMENT OF PSEUDOARTHROSIS IN CHILDREN USING ILIZAROV EXTERNAL - Rahman, Laila Maisarah A; Mohd Yusof, Nazri; Sulong, Ahmad Fadzli (International Journal of Allied Health Sciences, 2021)
Chronic osteomyelitis is an unfortunate condition that can lead to devastating complications among which are pathological fracture, non-union, and pseudoarthrosis. The management requires a long duration of antibiotic and follow-ups to gain skeletal consolidation. A two years eight months old girl presented with pseudoarthrosis of the right tibia after a history of pathological fracture secondary to chronic osteomyelitis. It initially started with a local abscess three months before chronic osteomyelitis changes. She failed conservative management with a full-length cast and was eventually treated with resection of the pseudoarthrosis, acute compression using peg technique and Ilizarov external fixator. After three months the fracture consolidated and Ilizarov external fixator was removed. However, she had an episode of fall leading to an undisplaced fracture of the tibia and was treated successfully with full length cast for two months. The management of pseudoarthrosis remains a challenge especially in dealing with bone and soft tissue defect and require meticulous planning before embarking on surgical intervention. It is proven widely that distraction osteogenesis through Ilizarov method stimulates the biosynthetic activity in tissues. Although the use of Ilizarov external fixator as skeletal stabilization in the management of chronic osteomyelitis is common in adult, it is uncommon in children. This is due to better healing potential in children and the fixator itself being bulky and require delicate care throughout its application. In conclusion, Ilizarov external fixator is an excellent option for skeletal stabilisation in the management of pseudoarthrosis in children. Keywords: Chronic Osteomyelitis, Ilizarov external fixator Acknowledgement: None of the authors has any financial, professional, or other conflicts to disclose.